Factors Affecting Urban Housing Development in Lusaka, Zambia - Chisumbe, Sampa; Aigbavboa, Clinton; Thwala, Wellington Didibhuku; Mwanaumo, Erastus (Alanya Üniversitesi, 2025)
This study investigates the factors affecting urban housing development in Lusaka, Zambia, a city facing significant challenges due to rapid urbanization and a high prevalence of inadequate housing. Utilizing the Delphi method, data was collected through two iterative rounds from a panel of 10 experts to identify and evaluate 15 factors contributing to poor housing outcomes. The findings reveal that political influence, poor linkage between infrastructure investment and service delivery, lack of access to affordable housing finance, weak urban governance, and high mortgage interest rates are the key factors impeding urban housing development in Lusaka. The study recommends developing an integrated housing planning framework, tailored housing finance products for low-income earners, and promoting governance principles to enhance transparency and accountability in housing development. This research provides valuable insights for policymakers and stakeholders in Sub-Saharan Africa, highlighting socio-economic areas requiring intervention to achieve sustainable urban housing development.